Ne faire qu'un seul peuple? Iroquois et Français à l'"âge héroïque" de la Nouvelle-France (1600-1660) - Beaulieu, Alain (Université Laval, 1992)
Keywords: Autochtones; Français; Iroquois

La fin des alliances franco-indiennes: enquête sur un sauf-conduit de 1760 devenu un traité en 1990 - Vaugeois, Denis (Boréal, 1995)
Keywords: Autochtones; Français

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

La Grande Paix de Montréal de 1701: les voies de la diplomatie franco-amérindienne - Havard, Gilles (Recherches amérindiennes au Québec, 1992)
Keywords: Autochtones; Français; Grande Paix de Montréal

CAMPBELL, FRANCIS WAYLAND - Milner, Elizabeth Hearn (Dictionnaire biographique du Canada, 1994)

BADGLEY, FRANCIS (1767-1841) - Senior, Elinor Kyte (Dictionnaire biographique du Canada, 1988)

Les drapeaux militaires en Nouvelle-France - Chartrand, René (Material History Review / Revue d’histoire de la culture matérielle, 1995)
Keywords: Armée

Lemoyne d'Iberville: A Soldier of New France - Crouse, Nellis Maynard (The Ryerson Press/Cornell University Press, 1954)
Keywords: Le Moyne d'Iberville et d'Ardillières, Pierre

Philippe de Rigaud de Vaudreuil, Governor of New France 1703-1725 - Zoltvany, Yves F (McClelland and Stewart, 1974)
Keywords: Gouverneurs; Rigaud de Vaudreuil, Philippe de

De la Champagne à la Nouvelle-France, Claude de Ramesay (1659-1724) - Litalien, Raymonde (Catalogue de l'exposition Le Canada de Louis XIV, 1980)
Keywords: Gouverneurs; Ramezay, Claude de

Un défenseur de la Nouvelle-France, François Piquet, le "Canadien" (1708-1781) - Chagny, André (Librairie Emmanuel Vitte, 1913)
Keywords: Autochtones; Communautés religieuses; Missions; Piquet, François; Sulpiciens

L'invasion du Canada en 1775, d'après les historiens canadiens-français - Kelly, John E. (Université Laval, 1941)
Keywords: Américains; Armée; Historiens

Dollard Des Ormeaux and the Fight at Long Sault: Was Dollard the Saviour of New France? - Lanctot, Gustave (Canadian Historical Review, 1932)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

La redoute de Dollard à la Baie des Sauvages. Un fort défendu par dix-sept Français - Barbeau, Marius (Revue canadienne de géographie, 1959)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Les officiers d'état-major des gouvernements de Québec, Montréal et Trois-Rivières sous le régime français - Roy, P.-G. (Revue canadienne, 1917)
Keywords: Armée

De la Nouvelle-Angleterre à la Nouvelle-France: l'histoire des captifs anglo-américains au Canada entre 1675 et 1760 - Fournier, Marcel (Société généalogique canadienne-française, 1992)
Keywords: Américains; Captifs